2021
DOI: 10.1007/s00338-021-02066-1
|View full text |Cite
|
Sign up to set email alerts
|

Symbiont shuffling across environmental gradients aligns with changes in carbon uptake and translocation in the reef-building coral Pocillopora acuta

Abstract: Symbiosis between reef-building corals and unicellular algae (Symbiodiniaceae) fuels the growth and productivity of corals reefs. Capacity for Symbiodiniaceae to fix inorganic carbon (Ci) and translocate carbon compounds to the host is central to coral health, but how these processes change for corals thriving in environmental extremes remains largely unresolved. We investigate how a model coral -Pocillopora acuta -persists from a reef habitat into an adjacent extreme mangrove lagoon on the Great Barrier Reef.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 77 publications
5
41
0
Order By: Relevance
“…Symbiodiniaceae taxa profoundly influence the physiology and stress resilience of their coral hosts ( Oliver and Palumbi, 2011 ; Howells et al, 2012 ; Suggett et al, 2017 ). We found distinct communities of Symbiodiniaceae associated with P. acuta between the reef and mangrove environments, which is in line with previous observations at this field site ( Ros et al, 2021 ). P. acuta colonies on the reef were largely dominated by the genus Cladocopium , whereas the mangrove colonies were dominated by the genus Durusdinium.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Symbiodiniaceae taxa profoundly influence the physiology and stress resilience of their coral hosts ( Oliver and Palumbi, 2011 ; Howells et al, 2012 ; Suggett et al, 2017 ). We found distinct communities of Symbiodiniaceae associated with P. acuta between the reef and mangrove environments, which is in line with previous observations at this field site ( Ros et al, 2021 ). P. acuta colonies on the reef were largely dominated by the genus Cladocopium , whereas the mangrove colonies were dominated by the genus Durusdinium.…”
Section: Discussionsupporting
confidence: 92%
“…distinct communities of Symbiodiniaceae associated with P. acuta between the reef and mangrove environments, which is in line with previous observations at this field site (Ros et al, 2021). P. acuta colonies on the reef were largely dominated by the genus Cladocopium, whereas the mangrove colonies were dominated by the genus Durusdinium.…”
Section: Reef Versus Mangrove Environmental Conditions Influence Coral-microbial Associationssupporting
confidence: 92%
See 2 more Smart Citations
“…For instance, it is welldocumented that different coral colonies of a given species, exposed to similar levels of thermal stress at the same location can exhibit varying degrees of bleaching (Swain et al 2016;Green et al 2019); however, we do not know if this mosaic of bleaching phenotypes observed at the colony-level is reflected in the microbiome. To address this question, we used the emerging model species Pocillopora acuta, a reef-building coral with well characterised ecology, reproduction and microbiome (Torda et al 2013a;Schmidt-Roach et al 2014a, b;Nakajima et al 2018;Damjanovic et al 2020b;Ros et al 2021). Previous studies have revealed that the microbiomes of Pocillopora species are generally stable under changing environmental conditions (Pogoreutz et al 2018;Epstein et al 2019), with species such as P. acuta often hosting site-specific microbiomes (Torres et al 2020), perhaps due to the brooding reproductive strategy of the host (Torda et al 2013a).…”
Section: Introductionmentioning
confidence: 99%